Indigenous Epistemologies in Tertiary Education - Edwards, Shane; Hewitson, Kieran (The Australian Journal of Indigenous Education, 2008)
Abstract This paper contends that Indigenous epistemologies in educational curriculum can serve as powerful counter hegemonic action to dominant discourses. It then discusses how the implementation and application of Indigenous epistemologies in adult educational curricula can support intellectual sovereignty and positive identity construction for Indigenous wellbeing.